Hydrogel based scaffolds in cardiovascular disease: applications in myocardial regeneration, biological pacing, and heart failure therapy - Tian, Jiakun; Yang, Huiling; Chang, Linlin; Zhang, Xu; Wang, Weitie; Li, Ranwei (Frontiers in Cell and Developmental Biology, 2025)
Cardiovascular diseases are the leading cause of morbidity and mortality worldwide. Current treatments for cardiovascular diseases have improved overall survival rates. However, there are several limitations in reversing left ventricular hypertrophy, preventing ischemia-reperfusion injury, and completely curing refractory heart failure. Tissue engineering, such as the use of hybrid scaffolds, provides a promising strategy for solving these problems and is used in cardiovascular diseases, especially in the treatment of myocardial infarction. Hydrogels are materials with unique 3D crosslinked polymer networks. They are composed of natural or synthetic hydrophilic polymers that contain many chemical components. Hydrogels serve as effective materials in drug delivery and tissue regeneration, achieving desired therapeutic effects for a range of diseases. This review aims to introduce the types of tissue engineering materials currently used, including natural and synthetic hydrogels. In addition, this review investigates the application of hydrogels in cardiovascular diseases such as myocardial infarction, biological pacing, myocardial regeneration, and heart failure.